2012
DOI: 10.1007/s12185-012-1210-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment outcome of invasive fungal infections in patients with hematological malignancies

Abstract: Invasive fungal infection (IFI) causes morbidity and mortality among patients with hematological malignancies who receive cytotoxic chemotherapy or hematopoietic stem cell transplantation (HSCT). We evaluated the incidence and treatment outcomes of proven and probable IFI in 22 institutions between 2006 and 2008 following the recent European Organization for Research and Treatment of Cancer/Mycosis Study Group (EORTC/MSG) consensus criteria. We analyzed 2,821 patients with hematological malignancies, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
3
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 34 publications
7
73
3
8
Order By: Relevance
“…was the most common causative agent in probable/proven IFI, supporting the previously reported data (17). The incidence of aspergillosis was 5.9%, which was slightly higher than that declared in other studies (0.8%-2.6%) (6,7,15). The environmental conditions of our clinic might have led to increased IFI rates, as longterm refurbishment studies might have exacerbated moldrelated fungal infections.…”
Section: Discussionsupporting
confidence: 89%
“…was the most common causative agent in probable/proven IFI, supporting the previously reported data (17). The incidence of aspergillosis was 5.9%, which was slightly higher than that declared in other studies (0.8%-2.6%) (6,7,15). The environmental conditions of our clinic might have led to increased IFI rates, as longterm refurbishment studies might have exacerbated moldrelated fungal infections.…”
Section: Discussionsupporting
confidence: 89%
“…Впоследниегодыотмеченростчисламикотиче-ских заболеваний у онкогематологических больных на фоне тяжелой нейтропении и/или проводимой иммуносупрессивнойтерапии [5,6].Этосвязаноссо-вершенствованием методов диагностики микозов, атакжесболее«агрессивными»схемамицитостати-ческойтерапии,широкимиспользованиемтрансплан-тациигемопоэтическихстволовыхклетоккак«терапии спасения».Известно,чтоуонкогематологическихболь-ныхосновнымиИМявляютсяИАимукормикоз [6][7][8].…”
Section: Discussionunclassified
“…Roden MM et al reported infection sites of mucormycosis in patients with malignancy. Respiratory accounts for the majority (60 %), gastrointestinal accounts for only 3 % [3]. Thus, in patients with malignancy, gastrointestinal mucormycosis is rare.…”
Section: American Journal Of Infectious Diseases and Microbiologymentioning
confidence: 99%